Molecular engineering of the alkyl chain in planar carbazole dyes toward efficient interfacial charge transfer processes. (13th November 2020) - Zhu, Qianqian; Zhang, Xiaomin; Pang, Zhihan; Wu, Wenjun; Liu, Bo
Abstract : With the extension of the alkyl chain, the interfacial charge transfer processes are effectively improved. Abstract : Alkyl chains are generally applied in organic dyes to prevent the unfavorable π-aggregation, affecting the photovoltaic performance of DSSCs to considerable extent. However, the effect of various alkyl chains on interfacial charge transfer processes has barely been investigated. Therefore, in this work, three novel carbazole dyes with various alkyl chains are designed and applied in DSSCs. Although the optical and electrochemical properties of the dyes are only slightly improved by the alkyl chains, all the interfacial charge transfer processes, including charge injection, dye regeneration, and charge collection, are effectively promoted first and then slightly restrained as the methyl group is gradually extended to the octyl group. Therefore, owning to the suitable length of the butyl groups, dye CS-39 presents the best photovoltaic performance among the four dyes, with a photocurrent density of 15.70 mA cm −2, a photovoltage of 0.765 V, a fill factor of 0.698, and a power conversion efficiency of 8.39%. As a result, the alkyl chain presents an obvious and complex effect on various interfacial charge transfer processes. Our results provide a reasonable strategy for the design of the appropriate alkyl chain to develop efficient organic sensitizers in the future.